Training On Formative And Summative Learning Evaluation For Early Childhood Educators At Himpaudi Kec. Pondok Kelapa Kab. Central Bengkulu - Haryono, Mimpira; Pebriani, Ela; Imran, Ranny Fitria (Universitas Dehasen Bengkulu, 2025)
This community service activity aims to improve the competence of PAUD educators in compiling formative and summative learning evaluations that are in accordance with the characteristics of early childhood. The training was carried out by lecturers of the PG-PAUD Study Program, Dehasen University, Bengkulu on May 10, 2025, at the HIMPAUDI Secretariat, Pondok Kelapa District, Central Bengkulu Regency. This activity was attended by 40 participants consisting of PAUD principals and teachers who are members of HIMPAUDI, Pondok Kelapa District. The training methods include interactive lectures, group discussions, evaluation instrument preparation practices, and reflection and question and answer sessions. The material was delivered by three speakers who are expert lecturers in the field of early childhood education evaluation, namely Dr. Mimpira Haryono, M.Pd., Ela Pebriani, M.Pd., and Ranny Fitria Imran, M.Pd. The results of the training showed that there was a significant increase in the participants' understanding and skills in compiling evaluation instruments such as observation sheets, development journals, and child portfolios. This training has a positive impact in building educators' awareness that evaluation is an important part of the learning process, as well as encouraging the implementation of authentic evaluation that supports children's holistic development. This activity recommends follow-up in the form of mentoring and further training to strengthen the implementation of learning evaluation in PAUD units.